Microsporidia and 'the art of living together' - Vávra, Jiří; Lukeš, Julius (Advances in parasitology, 2013)
Parasitism, aptly defined as one of the 'living-together' strategies (Trager, 1986), presents a dynamic system in which the parasite and its host are under evolutionary pressure to evolve new and specific adaptations, thus enabling the coexistence of the two closely interacting partners. Microsporidia are very frequently encountered obligatory intracellular protistan parasites that can infect both animals and some protists and are a consummate example of various aspects of the 'living-together' strategy. Microsporidia, relatives of fungi in the superkingdom Opisthokonta, belong to the relatively small group of parasites for which the host cell cytoplasm is the site of both reproduction and maturation. The structural and physiological reduction of their vegetative stage, together with the manipulation of host cell physiology, enables microsporidia to live in the cytosolic environment for most of their life cycle in a way resembling endocytobionts. The ability to form structurally complex spores and the invention and assembly of a unique injection mechanism enable microsporidia to disperse within host tissues and between host organisms, resulting in long-lasting infections. Microsporidia have adapted their genomes to the intracellular way of life, evolved strategies how to obtain nutrients directly from the host and how to manipulate not only the infected cells, but also the hosts themselves. The enormous variability of host organisms and their tissues provide microsporidian parasites a virtually limitless terrain for diversification and ecological expansion. This review attempts to present a general overview of microsporidia, emphasising some less known and/or more recently discovered facets of their biology.
Keywords: Host-Pathogen Interactions; Microsporidia; cytoplazma; Cytoplasm; zvířata; Humans; Microsporidiosis; interakce hostitele a patogenu; mikrosporidióza; lidé; Animals